Complement factor B activation in patients with preeclampsia. (June 2015) - Velickovic, Ivan; Dalloul, Mudar; Wong, Karen A.; Bakare, Olufunke; Schweis, Franz; Garala, Maya; Alam, Amit; Medranda, Giorgio; Lekovic, Jovana; Shuaib, Waqas; Tedjasukmana, Andreas; Little, Perry; et al.
Highlights: Activated complement fB, Bb, is increased in preeclamptic women, especially in African-American patients. Fetal cord blood levels of Bb were similar in patients with or without preeclampsia. A maternal immune response through fB may contribute to the pathogenesis of preeclampsia. Abstract: Preeclampsia is a leading cause of maternal and fetal morbidity and mortality. Bb, the active fragment of complement factor B (fB), has been reported to be a predictor of preeclampsia. However, conflicting results have been found by some investigators. We hypothesized that the disagreement in findings may be due to the racial/ethnic differences among various study groups, and that fB activation is significant in women of an ethnic minority with preeclampsia. We investigated the maternal and fetal levels of Bb (the activated fB fragment) in pregnant women of an ethnic minority with or without preeclampsia. We enrolled 291 pregnant women (96% of an ethnic minority, including 78% African-American). Thirteen percent of these were diagnosed with preeclampsia. Maternal venous blood was collected from all participants together with fetal umbilical cord blood samples from 154 deliveries in the 291 women. The results were analyzed using the Mann–Whitney U test and multivariate analyses. Maternal Bb levels were significantly higher in the preeclamptic group than in the nonpreeclamptic group. Levels of Bb in fetal cord blood were similar in both groups. Subgroup analyses of African-American patients' results confirmed the study hypothesis that there would be a significant increase in Bb in the maternal blood of the preeclamptic group and no increase in Bb in the fetal cord blood of this group. These results suggest that a maternal immune response through complement fB might play a role in the development of preeclampsia, particularly in African-American patients.